ANALYSIS OF THE SUBJECT BRANCH OF PUBLIC ADMINISTRATION OF THE RISKS OF EMERGENCY SITUATIONS - Kurilo, A. (Public administration and state security aspects, 2023)
The article is devoted to the analysis of the subject area of public emergency risk management. One of the activities of the State Emergency Service of Ukraine to reduce the risk and reduce the consequences of natural disasters, accidents and catastrophes is the creation of a system for monitoring and forecasting emergency situations and coordinating work in this field.